MO441: Dynamic Role of Macrophage-Inducible C-Type Lectin in the Process of AKI-to-CKD Transition. (3rd May 2022) - Wang, Cui; LV, Linli; Liu, Bicheng; Zhu, Xiaoxiao
Abstract: BACKGROUND AND AIMS: Acute kidney injury (AKI) is a global health concern associated with high morbidity and mortality, as well as a high risk of progression to chronic kidney disease (CKD). As a result of phenotype diversity and plasticity, macrophages are recognized as key regulators of kidney repair, regeneration, and fibrosis. Mincle (macrophage-inducible C-type lectin, Clec4e) was reported to promote and maintain inflammatory response in AKI. However, the specific role of Mincle in the AKI-to-CKD transition is still unclear. METHOD: In this study, WT and Mincle -/- mice were subjected to renal ischemia-reperfusion (I/R) injury (ischemia for 35 min) without resecting the right kidney and were analyzed on days 1, 3, 14 and 30 to explore the potential effects and mechanism of Mincle on renal inflammation and fibrosis. RNA-seq was performed on day 30 to detect underlying pathogenesis. RESULTS: Our results showed that after I/R injury, renal interstitial macrophages identified by F4/80 immunofluorescence staining were up-regulated from day 1. Then macrophages gradually increased over time and obviously infiltrated in injured kidney both on day 14 and day 30. Mincle was colocalized to renal macrophages in WT mice but was not detectable in Mincle -/- mice. RT-PCR suggested that Mincle start to increase on day 1 and reached the highest level on day 14, and then decreased on day 30 which was consistent with the immunofluorescence of Mincle. During the I/R induced AKI-to-CKD progression, we observed similar dynamic change patterns for proinflammatory cytokines and fibrosis markers and Mincle expression in WT mice. Of note, on day 30, we found that Mincle deletion aggravated renal inflammatory response as detected by inflammatory cytokines like MCP-1, IL-6 and IL-1β. Renal fibrosis also deteriorated in Mincle -/- mice with increased mRNA expression of TGF-β, fibronectin and collagen I. Quantitative Masson staining and immunofluorescent α-SMA further confirmed more kidney fibrosis in Mincle -/- mice than WT mice. Then we performed gene set enrichment analysis (GSEA) of the differentially expressed genes in two groups on day 30 and identified enriched toll-like receptor signaling and NF-κ-B signaling in Mincle -/- mice indicating more activated inflammatory responses. RNA-seq also showed top 5 significantly up-regulated genes ( Slpi, Cd79a, Jchain, Lyz1 and Mzb1 ) related to the immune response in the context of Mincle deficiency, among which secretory leukocyte protease inhibitor (SLPI) showed 60-fold higher expression compared with WT mice. Next, increased SLPI mRNA expression was confirmed by RT-PCR in I/R kidney in Mincle -/- mice compared to the WT group. And increased SLPI positive cells in fibrotic kidneys after I/R at day 14 and day 30 in Mincle -/- mice was also observed, suggesting its potential role in renal fibrosis caused by Mincle deletion. CONCLUSION: To conclude, Mincle may exert a sustaining effect on the long-term outcome of the AKI-to-CKD transition through modulating inflammation and fibrosis. Clarifying the specific function of Mincle positive macrophages during the process of AKI-to-CKD transition may provide new insight into the underlying mechanism of CKD progression.